2022
DOI: 10.1111/ijmr.12296
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness: Unpacking its three shades and illuminating integrative ways to understand the construct

Abstract: Over time mindfulness research and practice has taken on diverse basic assumptions and theoretical traditions, and the pseudo‐scientific use of the term has become more prevalent. Given the ubiquitousness of both personal and professional applications of mindfulness, the need for a thorough understanding of its theoretical cornerstones is necessary. In this review, we use bibliometric techniques to uncover the field's intellectual roots (Study 1), and document bibliographic coupling analysis to illuminate curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 189 publications
5
19
0
Order By: Relevance
“…Metacognitive practice is the underlying processes monitoring information and experience, e.g. the way we perceive and conceptualise information and experiences, enhancing the development of mindfulness through practice (Daniel et al ., 2022). As such, sensemaking, done retrospectively and a function of metacognition, is about interpreting events in such a way so as to articulate the meaning thereof in a way that it can be used as a platform for going forward (de Klerk, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Metacognitive practice is the underlying processes monitoring information and experience, e.g. the way we perceive and conceptualise information and experiences, enhancing the development of mindfulness through practice (Daniel et al ., 2022). As such, sensemaking, done retrospectively and a function of metacognition, is about interpreting events in such a way so as to articulate the meaning thereof in a way that it can be used as a platform for going forward (de Klerk, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These metaphors are a representation of metacognitive application. Studies have indicated, for example, that mindfulness interventions and mindfulness practice in recovery processes, provides benefits to psychological detachment, sleep quality and quantity and perceived exhaustion (Daniel et al ., 2022). Further studies indicate that metacognition practices such as mindfulness provide a buffering role of trait and state mindfulness in the relationship between work stressors (e.g., workload, organisational constraints and experienced incivility; or quantitative and emotional job demands) and well-being/strain (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Mindfulness is a useful concept for better understanding consumers' perceived value (Mick, 2017), such as the value of processing marketing information or the value of interpreting information (Daniel et al, 2022). Mindful consumers process information concerning the service attributes in an efficient (Daniel et al, 2022) and objective way (Ndubisi, 2014), which allows customers to easily identify the value of the service provided (Daniel et al, 2022;Ndubisi, 2014). Being attentive to the moment-to-moment experience makes the benefits of the services more visible to customers (Daniel et al, 2022).…”
Section: Mindfulness and Service Valuementioning
confidence: 99%
“…Mindful consumers process information concerning the service attributes in an efficient (Daniel et al, 2022) and objective way (Ndubisi, 2014), which allows customers to easily identify the value of the service provided (Daniel et al, 2022;Ndubisi, 2014). Being attentive to the moment-to-moment experience makes the benefits of the services more visible to customers (Daniel et al, 2022). Thus:…”
Section: Mindfulness and Service Valuementioning
confidence: 99%